Observational Surveillance Approach to Detect Novel Work-Related Diseases and Hazards: An Application to a Belgian Occupational Health and Safety Database. Issue 9 (September 2018) - Bosson-Rieutort, Delphine; Schouteden, Martijn; Godderis, Lode; Bicout, Dominique J.
Abstract : Objectives: Rapid changes in working conditions give rise to new occupational health risks. We applied the Spectrosome approach, a network-based analysis, to investigate associations between disease and multiple occupational exposures. Methods: We investigated work and health's associations in a specific sector: the agricultural sector and for a specific and frequent health complaint: sore throat; using PRECUBE dataset of the Belgian Occupational Health and Safety, containing 381.615 occupational health observations. We compared the results of the spectrosome with classic frequency analyses. Results: Spectrosome approach reports more significant signals of multiple associations of agents compare to the frequency analysis. Conclusion: This difference justifies the usefulness of taking into account the multiplicity of causes leading to a health event, which is a clear asset of the Spectrosome method. Abstract : Supplemental Digital Content is available in the text